The Burden Of Physical Gender Based Violence In Uganda - Economic Policy Research Centre (Economic Policy Research Centre, 2020)
This brief uses the 2016 UDHS survey to shed light on factors that perpetuate physical gender based violence (GBV). Results of the survey reveal that much of the physical violence is predominantly perpetuated by intimate partners. Women with low education and income are more vulnerable to physical violence in intimate relationships. At the same time, the presence of dependents within the household increases the likelihood of physical violence. We recommend economic empowerment for women through education and skill training in order to address the impacts of physical violence.